Kinetics of Reaction between Dimethyl Sulfide and Hydrogen in Black Liquor Gasification Gas with ZnO Catalyst - Nong, G.Z.; Wang, S.F.; Mu, J.J.; Zhang, X.L. (Asian Journal of Chemistry, 2012)
Black liquor gasification gas contains a small amount of dimethyl sulfide, which needs to be removed before the gasification gas combusting in the gas turbine in black liquor integrated gasification combined cycle (BLIGCC). A desulphurization method has been carried experimentaly in the conditions of high temperature and ZnO catalyst, where dimethyl sulfide and hydrogen reacted to produce methane and hydrogen sulfide, then the hydrogen sulfide was absorbed with alkali solution. The current investigation was carried out to find the kinetics of reaction between dimethyl sulfide and hydrogen in black liquor gasification gas with ZnO catalyst. The reaction was studied in a pipe reactor at various temperatures and concentrations of dimethyl sulfide and hydrogen. The reaction rate was evaluated by analyzing the consumption of dimethyl sulfide and then the rate law was established. The reaction has been found 0.963 and 1.098 order with respect to dimethyl sulfide and hydrogen, respectively and the activation energy was 31737.19 J mol with frequency factor 16747.32.